RELATIONSHIP BETWEEN UNATTENDED AND ATTENDED BP VALUES AND PRECLINICAL ORGAN DAMAGE. (June 2018) - Salvetti, M.; Paini, A.; Bertacchini, F.; Stassaldi, D.; Maruelli, G.; Cappellini, S.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: It has been suggested that measurement of "unattended" or "automated oscillatory (AOBP)" blood pressure values may provide advantages over conventional BP measurement; some hypertension guidelines now suggest this approach as the preferred one for measuring office BP. Data on the relationship between AOBP and cardiovascular events are much less solid as compared to those obtained with the standard BP measurement; on the other hand, some study suggested that AOBP might be more strictly correlated with hypertensive target organ damage than "attended" BP. The aim of our study was to evaluate the relationship between "attended" or "unattended" BP values and target organ damage in 261 subjects attending the outpatient clinic of an ESH Excellence Centre. Design and method: BP values were measured by the physician with an automated oscillometric device (Omron HEM 9000Ai, mean of 3 measurements), after 5 minutes of rest; thereafter, the patient was left alone and unattended BP was measured automatically after 5 minutes (3 measurements at 1 minute interval). Results: Patient's mean age was 61 ± 16 yrs, mean BMI 26.1 ± 4.2, 60% were female, 88 % had a previous diagnosis of hypertension (64% treated). Systolic unattended BP was lower as compared to attended SBP (130.1 ± 15.7vs138.6 ± 17.2 mmHg). Left ventricular mass index (LVMI) was similarly correlated with unattended and attended SBP (r = 0.132 and r = 0.133, p < 0.05, respectively). LVMI was similarly correlated with unattended and attended pulse pressure (PP) (r = 0.277 and r = 0.299, p < 0.05, respectively). Carotid IMT was significantly and similarly correlated with both attended and unattended BP values (CBMaxIMT: r = 0.172 and r = 0.153 for attended and unattended SBP, p < 0.05 and: r = 0.459 and r = 0.436 for attended and unattended PP, p < 0.001). The differences between correlations were not statistically significant. Conclusions: Measurement of BP "unattended" or "unattended" provides different values, being unattended BP lower as compared to attended BP. Our results suggest that attended and unattended BP values are similarly related with cardiac and vascular hypertensive target organ damage.